2022
DOI: 10.1002/jmv.28406
|View full text |Cite
|
Sign up to set email alerts
|

In silico study of SARS‐CoV‐2 spike protein RBD and human ACE‐2 affinity dynamics across variants and Omicron subvariants

Abstract: The coronavirus disease 2019 virus outbreak continues worldwide, with many variants emerging, some of which are considered variants of concern (VOCs). The WHO designated Omicron as a VOC and assigned it under variant B.1.1.529. Here, we used computational studies to examine the VOCs, including Omicron subvariants, and one variant of interest.  Here we found that the binding affinity of human receptor angiotensin‐converting enzyme 2 (hACE2) and receptor‐binding domain (RBDs) increased in the order of wild type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…During the SARS-CoV-2 pandemic, computational approaches effectively assist researchers to predict protein-protein interactions and screening possible drugs faster. Abeywardhana et al used computational studies to examine the binding affinity of ACE2 and several variants, they found that Omicron BA.2 shows the highest binding capacity to the ACE2 [ 23 ]. Mondeali et al studied the interactions of the S477N-ACE2 in silico and revealed an increased binding affinity of N477 for ACE2 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the SARS-CoV-2 pandemic, computational approaches effectively assist researchers to predict protein-protein interactions and screening possible drugs faster. Abeywardhana et al used computational studies to examine the binding affinity of ACE2 and several variants, they found that Omicron BA.2 shows the highest binding capacity to the ACE2 [ 23 ]. Mondeali et al studied the interactions of the S477N-ACE2 in silico and revealed an increased binding affinity of N477 for ACE2 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abeyardhana et al found that the binding a nity of ACE-2 receptor and RBD domain increased in the order of Wuhan < Beta < Alpha < BA.5 < Gamma < Delta < BA.2.75 < BA.1 < BA.3 < BA.2. Interactions between docked complexes revealed that the RBD residue positions like 452, 478, 493, 498, 501, and 505 were crucial in creating strong interactions with ACE-2 [25]. Omicron BA.2 shows the highest binding capacity to the ACE-2 receptor among all the mutant complexes studied.…”
Section: Discussionmentioning
confidence: 95%
“…Omicron BA.2 shows the highest binding capacity to the ACE-2 receptor among all the mutant complexes studied. The L452R, F486V, and T478K mutations in the spike of BA5 signi cantly impacted the interaction network in the BA.5 RBD-ACE2 interface [25].…”
Section: Discussionmentioning
confidence: 99%
“…Since December 2021, the SARS-CoV-2 Omicron variant has rapidly preempted the shares of other VOCs like the Delta and Gamma variants and become the predominant variant globally. The enhanced ability of the Omicron variant to evade vaccine or infection-induced immunity and bind with angiotensinconverting enzyme 2 receptor confers its exceedingly potent infectivity and high odds of reinfection and breakthrough infection (18,26,27). Moreover, more and more countries canceled their previously strict COVID-19 management, thus leading to a surge of infected cases.…”
Section: Discussionmentioning
confidence: 99%